2006
DOI: 10.1002/mrd.20580
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of extracellular matrix at ovulation of the bovine ovarian follicle

Abstract: Using immunohistochemistry and RNA analyses we examined the fate of components of a newly identified matrix that develops between granulosa cells (focimatrix, abbreviated from focal intraepithelial matrix) and of the follicular basal lamina in ovulating bovine ovarian follicles. Pre- and postovulatory follicles were generated by treatment with estradiol (Day 1), progesterone (Days 1-10), and prostaglandin analogue (Day 9) with either no further treatment (Group 1, n = 6) and or with 25 mg porcine LH (Day 11, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
(59 reference statements)
4
35
0
1
Order By: Relevance
“…Heparanase is an endoglycosidase that cleaves polymeric heparan sulphate molecules from large HSPG. It was recently demonstrated that LH stimulated a rapid increase in heparanase mRNA and protein concentrations in the bovine granulosa cells (Klipper et al 2009) and this could explain the disappearance of perlecan from collapsed follicles shortly after ovulation (Irving-Rodgers et al 2006). This would then stimulate the release of sequestered factors such as FGF2 and heparan sulphates, thereby facilitating endothelial invasion.…”
Section: Periovulatory Events: the Breakdown Of The Basement Membranementioning
confidence: 97%
See 2 more Smart Citations
“…Heparanase is an endoglycosidase that cleaves polymeric heparan sulphate molecules from large HSPG. It was recently demonstrated that LH stimulated a rapid increase in heparanase mRNA and protein concentrations in the bovine granulosa cells (Klipper et al 2009) and this could explain the disappearance of perlecan from collapsed follicles shortly after ovulation (Irving-Rodgers et al 2006). This would then stimulate the release of sequestered factors such as FGF2 and heparan sulphates, thereby facilitating endothelial invasion.…”
Section: Periovulatory Events: the Breakdown Of The Basement Membranementioning
confidence: 97%
“…It is curious that the accumulation of VEGFA in the granulosa is unable to stimulate protease activity and enable the migration of endothelial cells into the granulosa layer. This is presumably due to the more complex composition of the follicular basement membrane (mainly collagen type IV, laminin a1, b1 and b2 as well as nidogen, perlecan and focimatrix), while the ECM associated with the vasculature is principally composed of collagen IV and laminin b2 (Irving- Rodgers et al 2006).…”
Section: Pre-ovulatory Folliclementioning
confidence: 99%
See 1 more Smart Citation
“…Focimatrix in the cow is composed of aggregates of basal lamina material (collagen type IV a-1 (COL4A1) and a-2, laminin chains a-1, b-2 (LAMB2) and g-1, perlecan (HSPG2), and nidogens 1 and 2 (NID1 and -2). It is degraded at ovulation (Irving- Rodgers et al 2006a) as granulosa cells commence terminal differentiation into luteal cells and hence does not exist in human or bovine corpora lutea (Irving- Rodgers et al 2004Rodgers et al , 2006b. Thus, focimatrix is developmentally regulated and is present before, and then during, the follicular phase when granulosa cells mature to produce progesterone and oestradiol and at the same time when follicles become dominant or subordinate.…”
Section: Introductionmentioning
confidence: 99%
“…The function (Yang&Fortune, 2006) and the structure (Rodgers&Irving- Rodgers, 2010) of the bovine ovary has been extensively studied. Also, the granulosa cells and the extracellular matrix of bovine follicles of various developmental stages are well described (Lavranos et al, 1994;Irving-Rodgers et al, 2006).…”
Section: Cowmentioning
confidence: 99%